Research Methods in Early Childhood / An Introductory Guide - Albon Deborah; Mukherji Penny (Sage Publications, 2010)
This book is tailored to meet the needs of Early Childhood Students. Introduction, Paradigms and Principles, Positive Research, Interpretivism and Post-Structuralism, Ethics, Listening to Young Children, Approaches to Research, Surveys, Ethnography, Case Studies, Action Research, Methods, Observation, Interviews, Questionnaires, Using Documents and Other Visual ''Texts'', Journaling as a Research Tool, Creative Methods for Listening to Children in Research, Carrying out a Research Project, Research Design, Reviewing the Literature, Analyzing and Presenting Data, Writing up, Conclusion, Glossary, Bibliography, Index.